PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA - Crystha Armereo; Pipit Fitri Rahayu (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
This writing was carried out with the aim of examining the effect of Current Ratio, Net Profit Margin, Debt to Equity Ratio, on Profit Growth in Hotel, Restaurant and Tourism Subsector Companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. Researchers used quantitative research methods and analytical techniques used in this study, namely analyzing multiple linear regression. Sampling used a purposive technique for a total population of 13 companies and a final sample of 39 during the 2019-2021 period. Disclosure research results: (1) Current Ratio has no effect on profit growth. (2) Net Profit Margin affects profit growth. (3) Debt to Equity Ratio has no effect on profit growth. profit growth.Keywords: Current Ratio, Net Profit Margin, Debt To Equity Ratio, Profit Growth